Effects of using Local feed resources on Growth performance of Lao native pigs - PHONEYAPHON, Vanhnasin; CHANTHAKOUN, Vongpasith; INTHAPANYA, Sangkhom; NAOYENG, Khamkeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This study was carried out to determine the extent to which protein-enriched cassava root (PECR) could replace ensiled taro foliage as the protein source for recently weaned (or Lao native pigs??) fed ensiled cassava root as the source of carbohydrate. Twelve female pigs of local breed (Moo Lat??) with average initial live weight of 8 kg were allocated to 4 treatments in a completely randomized block design with 3 replications. The treatments were: T1: Rice bran 50% + corn 20% + Ensiled Taro foliage 30%; T2: Rice bran 50% + corn 20% + Protein-enriched cassava root 30%; T3: Rice bran 50% + corn 20% + Fresh water spinach 30%; T4: Rice bran 80% + corn 20%. All treatments were used 12% of cude protein of formula feed. The results showed that total diet washigher for T3 = 43.29 kg, T1 = 41.88 kg, T4 = 40.85 kg and lower for T2 = 40.18 kg (P-value <0.05). - Intake, (kg/day/pig) was higher for T3 = 515.4 kg/day/pig, T1 = 498.7 kg/day/pig, T4 = 486.3 kg/day/pig and lower for T2 = 478.44 kg/day/pig, (P- value <0.05). - Average Daily Gain (ADG) was higher for T3 = 224.3 g/day, T1 = 221.4 g/day, T4 =185.1g/day and lower for T2 = 175.9g/day, (P- value <0.05). - Feed Conversion Ratio (FCR) was better for T1 = 2.3, T3 = 2.3, T4 = 2.6 and then for T2 = 2.7, respectively (P-value <0.05). - Life Weight gain was higher for T1 = 7.43 kg / kg, T3 = 7.26 kg / kg, T4 = 6.13 kg/kg and lower for T2 = 5.8 kg / kg, (P-value <0.05). - Initial weight (kg) and final weight (kg) were not different values among the treatments - The economic returns from this experiment was not differed among the treatments, but the net income was higher for T1 = 104,085 kip /pig, than other treatments from T2 = 99,218kip / pig, T3 = 98,793kip / pig and T4 = 98,667kip / pig respectively.